A concessão administrativa nos serviços públicos de saúde - Lopes, Cintia Barudi (2017)
The theme of this thesis is the administrative concession in the field of public health in Brazil. The purpose of this research is to analyze whether the contractual model of public-private partnerships of Federal Law 11,079 of 2004 in the form of administrative concession can be compatible with the actions and services of the Unified Health System and, consequently, Whether this hiring can be celebrated for the management of clinical medical hospital services. One of the great obstacles to this private alternative of offering public health services is the fact that it is extracted from the constitutional text that the participation of non-state entities in SUS actions and services is complementary. One of the assumptions of the research is to establish a differential between the administrative concessions made in the health sector and the other models of private offering of this service through the Unified System. The research also intends to address the issue of the complementarity of private participation in SUS actions and services and, if this characteristic, has the effect of preventing the conclusion of PPPs in the sector. The problem was tackled based on the specific doctrine and decisions recently issued by the Federal Supreme Court that allowed for the best interpretation of the constitutional provisions on the matter, as well as helping to identify the effective legal advantages obtained by the Government in the adoption of the model Of public-private partnerships in clinical health. The research is finished listing the conclusions that were obtained during the study regarding the private participation through administrative concession in the Unified Health System